2016
DOI: 10.1016/j.lungcan.2016.07.019
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, double-blind, phase II study of ramucirumab plus docetaxel vs placebo plus docetaxel in Japanese patients with stage IV non-small cell lung cancer after disease progression on platinum-based therapy

Abstract: Second-line ramucirumab-docetaxel improved PFS similar to that seen in the REVEL trial with a manageable safety profile in Japanese patients with NSCLC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
83
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(93 citation statements)
references
References 16 publications
7
83
3
Order By: Relevance
“…In our study, the ORR of DR in the 29 patients administered prophylactic PEG‐G‐CSF appeared to be similar to that of previous studies . Although the efficacy and safety of DR in patients with NSCLC aged > 75 years is unclear, our study indicated that DR is active and tolerable in elderly patients if prophylactic PEG‐G‐CSF is administered.…”
Section: Discussionsupporting
confidence: 88%
“…In our study, the ORR of DR in the 29 patients administered prophylactic PEG‐G‐CSF appeared to be similar to that of previous studies . Although the efficacy and safety of DR in patients with NSCLC aged > 75 years is unclear, our study indicated that DR is active and tolerable in elderly patients if prophylactic PEG‐G‐CSF is administered.…”
Section: Discussionsupporting
confidence: 88%
“…And the association between HR OS and 12-month OS milestone ratio appeared to be stronger for secondline studies (R 2 = 0.89;95%CI, 0.72-0.98) than for first-line studies (R 2 = 0.65; 95% CI, 0.20-0.91). Meanwhile, in second-line NSCLC trials that published between 2013 and 2017, [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] the median time frame needed for the interim analysis of OS was 28 months (range: 20-48 months), while it was 12 months for 1 yr survival analysis. Collectively, these results indicate the potential of 1 yr survival as a valid SE for OS in second-line NSCLC trials.…”
Section: Discussionmentioning
confidence: 99%
“…12 Although their study did not provide a rigorous SE assessment, their results indicated the potential surrogacy of 1 yr survival for OS in advanced NSCLC. For the second condition, we performed a pre-analysis of recently published (2013-2017) second-line NSCLC trials [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] (Supporting Information Table S1). In the pre-analysis, the time frame needed for the interim analysis of OS in each trial was extracted from the published articles or ClinicalTrials.gov to calculate the median time frame.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, a number of different compounds were used to treat our patients, shown in Table 2. Furthermore, ramucirumab has been approved for the second-line treatment of metastatic NSCLC in combination with docetaxel [34,35], and would therefore be more effective than docetaxel monotherapy as a second-line chemotherapy, except when contraindicated. Recent studies have shown that, after platinum-based chemotherapy failure in patients with NSCLC, monoclonal antibodies against programmed cell death 1 (PD-1) or PD ligand (PD-L1) demonstrate superior OS when compared with standard chemotherapy [36,37,38,39].…”
Section: Discussionmentioning
confidence: 99%